Performance evaluation of industrial scale fluidized bed paddy dryer - Ibrahim, Mohd Nordin; Sarker, Md. Sazzat Hossain; Ab. Aziz, Norashikin; Punan, Mohd Salleh (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Field investigation on industrial scale fluidized bed paddy drying in a processing plant of Padiberas Nasional Berhad (BERNAS) was carried out to asses drying characteristics, energy consumption and final quality of product during two paddy harvesting seasons. For the first season (August-September), average drying rate was found to be 538 kg/hr to reduce paddy moisture content from 36.98± 0.89% dry basis (db) to 27.58±0.79% db at 100-120 °C drying air temperature and 2.24 m/s bed air velocity with a feed rate of 7.75 t/hr. Meanwhile, in another season (February-March), average drying rate was found to be 435 kg/hr to reduce paddy mc from 28.14 ±0.68 % db to 22.54 ± 0.69% db at 78-90 °C drying air temperature and 2.24 m/s bed air velocity with a feed rate of 9.5 t/hr. The thermal and electrical energy consumptions in terms of primary energy in MJ/kg water removed were obtained as 7.57 and 0.97, respectively for the first season and 5.92 and 1.2 for the second season. Higher head rice yield and whiteness, and lower milling recovery were achieved during first season than second season at acceptable milling degree and transparency. Although less than expected throughput capacity resulted in lower performance of the dryer yet high moisture paddy drying with fluidized bed dryer using high temperature yielded high drying rate and product quality.